2015
DOI: 10.4238/2015.may.11.14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of highly expressed host microRNAs that respond to white spot syndrome virus infection in the Pacific white shrimp Litopenaeus vannamei (Penaeidae)

Abstract: ABSTRACT. MicroRNAs (miRNAs) are known to play an important role in regulating both adaptive and innate immunity. Pacific white shrimp (Litopenaeus vannamei) is the most widely farmed crustacean species in the world. However, little is known about the role miRNAs play in shrimp immunity. To understand the impact of viral infection on miRNA expression in shrimp, we used high-throughput sequencing technology to sequence two small RNA libraries prepared from L. vannamei under normal and white spot syndrome virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In animals, miRNAs regulate their target genes through mRNA destabilization and translational inhibition (Bushati and Cohen 2007). So far, miRNAs have been identified in a few aquatic crustacean species, and these were involved in regulation of oocyte meiosis , adaptive immunity Ou et al 2012;Zeng et al 2015), and drug response (ValenzuelaMiranda et al 2015). Previous reports have shown that some plant miRNAs respond to salinity stress and that some miRNA targets are salt stress-related genes (Xie et al 2014;Peng et al 2014;Frazier et al 2011).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In animals, miRNAs regulate their target genes through mRNA destabilization and translational inhibition (Bushati and Cohen 2007). So far, miRNAs have been identified in a few aquatic crustacean species, and these were involved in regulation of oocyte meiosis , adaptive immunity Ou et al 2012;Zeng et al 2015), and drug response (ValenzuelaMiranda et al 2015). Previous reports have shown that some plant miRNAs respond to salinity stress and that some miRNA targets are salt stress-related genes (Xie et al 2014;Peng et al 2014;Frazier et al 2011).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In some articles about crustaceans’ microRNA sequencing, D . pulex genome was often chosen as the reference to analyze sequencing results [ 2 , 7 , 14 , 15 ]. In present paper, the small RNA tags were mapped to the D .…”
Section: Methodsmentioning
confidence: 99%
“…The information pertaining to research on noncoding RNAs in the shrimp is very limited. Zeng et al (2015) carried out the work on identification of highly expressed host micro-RNAs that respond to WSSV infection in the shrimp L. vannamei.…”
Section: Identifying Gene Associated Markers and Noncoding Rna Techmentioning
confidence: 99%
“…Furthermore, they reported that among the total SNPs they analysed, some of them showed polymorphism which may be closely related to the mutation that affect the important traits such as resistance to diseases and reproductive performance. Zeng et al (2015) carried out the work on identification of highly expressed host micro-RNAs that respond to WSSV infection in the shrimp L. vannamei. Such information will be also useful in developing programmes aiming the genetic improvement of the aquaculture species.…”
mentioning
confidence: 99%